2019
DOI: 10.1530/ec-19-0325
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and long-term outcomes of growth hormone therapy with easypod™ in pediatric subjects: Spanish ECOS study

Abstract: Background Non-adherence to r-hGH treatments occurs in a variable percentage of subjects. One problem found when evaluating adherence is the great variability in methods of detection and definitions utilized in studies. This study assessed the level of adherence in subjects receiving r-hGH with the easypod™ electronic device. Methods National, multicenter, prospective and observational study involving 238 subjects (144 with GH deficiency (GHD), and 86 with small for gestational age (SGA), 8 with Turner Syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 31 publications
3
27
1
Order By: Relevance
“…In the present study, the observed adherence rate was above 80% up to 3 years of clinical follow-up, which contrasts with the expected adherence rate of 55–65% observed in other studies using different r-hGH delivery technologies [ 22 , 23 ] and confirms the findings of other reports with the same methodology [ 5 , 6 , 13 , 14 , 24 ]. Additionally, this study suggests that adherence to therapy is predictor of clinical response, a factor that has been described in other scenarios where electromechanical auto-injectors are used to deliver drugs and to assess compliance to therapy [ 25 − 30 ].…”
Section: Discussioncontrasting
confidence: 68%
“…In the present study, the observed adherence rate was above 80% up to 3 years of clinical follow-up, which contrasts with the expected adherence rate of 55–65% observed in other studies using different r-hGH delivery technologies [ 22 , 23 ] and confirms the findings of other reports with the same methodology [ 5 , 6 , 13 , 14 , 24 ]. Additionally, this study suggests that adherence to therapy is predictor of clinical response, a factor that has been described in other scenarios where electromechanical auto-injectors are used to deliver drugs and to assess compliance to therapy [ 25 − 30 ].…”
Section: Discussioncontrasting
confidence: 68%
“…The multi-national easypod connect observational study (ECOS) assessed adherence among pediatric patients using the easypod connect system for GH therapy for up to 5 years. Adherence was ≥80% for more than 3 years for results overall and for several individual countries, and analyses showed significant associations between poor adherence and impaired clinical outcomes (112)(113)(114)(115)(116)(117). Adherence rates for patients new to GH therapy and those already receiving GH did not differ, and there was no difference between diagnoses (112).…”
Section: Digital Technologies For Adherence To Gh Therapymentioning
confidence: 94%
“…The ECOS assessed the adherence to recombinant human growth hormone treatment as well as growth outcomes in pediatric patients with growth disorders. The results of the European and American countries involved in this open-label, observational, longitudinal study have been published [ 20 - 22 ]. To our knowledge, there is no literature exploring the adherence to growth hormone treatment in Taiwanese or Chinese pediatric patients in a real-life setting, especially by using an electronic monitoring method.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the ECOS have been published by Koledova et al [ 19 ]. Among the countries involved, the results of Spain [ 20 ], Italy [ 21 ], and Mexico [ 22 ] have been published. However, there is no related publication in the Asia-Pacific region.…”
Section: Introductionmentioning
confidence: 99%